Analisis Faktor-faktor Yang Mempengaruhi Rendahnya Pembiayaan dengan Akad Istishna pada Perbankan Syariah - Adatha Aisyah Wijayanti; Bambang Waluyo; Dede Abdul Fatah (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2021)
This research aims to analyze the factors that influence the low level of financing with istishna contract in Islamic Banking in Indonesia. It is motivated by istishna’s financing which actually has a considerable potential for use in Indonesia, given that Indonesia is actively working on infrastructure development. However, the istishna contract is currently a financing that is rarely applied by Islamic Banking compared to other contract financing. This research is a qualitative descriptive study. The data used was primary data derived from interviews with employees of Islamic Banking who apply istishna’s financing. The data analysis technique used was interactive model analysis. The results showed that the factors that influenced the low istishna financing are istishna contract having high financing risks, there are alternative contracts that make istishna contract not a priority, risk of a failure developers, sharia bank business strategies, and moral standards of customers and developers.